Погляд крізь сторіччя: етнографічні студії в селі Оскіл на Харківщині - Іванчишен, В. (Народна творчість та етнологія, 2019)
До наукового обігу вводяться архівні етнографічні матеріали, що стосуються етнокультури мешканців с. Оскіл Ізюмського району Харківської області, які були записані наприкінці 1920‑х років і у 2017 році. Це стосується архівної одиниці збереження ф. 1 «Етнографічна комісія» під номером 365 «Червоно-Оскілька артіль на Ізюмщині», у якій зібрано унікальні етнографічні відомості з царини етнокультури слобідських українців. Експедиція здійснювалася науковими співробітниками Інституту мистецтвознавства, фольклористики та етнології ім. М. Т. Рильського НАН України на теренах Слобідського краю, переважно Харківщини, упродовж жовтня 2017 року. З огляду на матеріали архівної справи 1920‑х років, доцільним видалось обрання с. Оскіл на Ізюмщині для сучасного дослідження та компаративного аналізу результатів. Крім того, вказаний населений пункт є одним з найбільш населених у цьому районі, що підсилило актуальність вивчення, адже уможливило чисельність респондентів різної вікової категорії. Опираючись на завдання зазначеного експедиційного виїзду, виникла необхідність повторного (на основі запитальників 1920‑х рр.) сучасного опитування мешканців с. Оскіл з метою виявлення тенденцій переривання / тяглості історичної пам’яті жителів населеного пункту, збереження етнокультурних явищ та окреслення рис етнографічних реалій, які трансформувались чи виникали упродовж ХХ – на початку ХХІ ст. На прикладі різних царин традиційної культури показано історичну спадкоємність основних її маркерів. Зокрема, це стосується зрізів господарсько-виробничої культури, ремесел та промислів, народної архітектури, етномедицини, поминально-поховальної обрядовості та ін. Таким чином, обидва етнографічні матеріали є яскравими відбитками етнокультурної спадщини українців с. Оскіл на Ізюмщині. Хоча вони записані з інтервалом майже в сто років, можна констатувати історичну тяглість збереження народної пам’яті щодо подій минулого століття, маркерів матеріальної та духовної культури слобожан. Archival ethnographic materials concerning the ethnic culture of the inhabitants of the village of Oskil, Izium district, Kharkiv region, recorded in the late 1920s and 2017, are introduced into the scientific circulation. It pertains to the archive unit of preservation under the number 365, The Artel from Chervonyi Oskil in Izium Region from the first fund Ethnographic Commission. The unit of preservation contains unique ethnographic facts from the area of the ethnic culture of the Ukrainians from Slobozhanshchyna. An expedition was conducted in October 2017 by the scientists of the M. Rylskyi Institute of Art Studies, Folkloristics and Ethnology on the territory of Slobozhanshchyna, mainly in the Kharkiv region. Taking into consideration the archival materials of the 1920s, it seems to be expedient to choose the village of Oskil in the Izium region for modern research and comparative analysis of the results. Besides, the settlement mentioned is one of the most populated ones in this district. It has strengthened the relevance of the study, as it enables the number of respondents from different age groups. According to the task of the expedition, the necessity for a repeated (based on the 1920s questionnaires) modern survey of the inhabitants of the village of Oskil has arisen. It is aimed at the detection of the tendencies of the brokenness/continuance of the historical memory of the settlement residents, the preservation of ethnic and cultural phenomena, and the identification of the features of ethnographic realities that have been transformed or appeared during the 20th and early 21st centuries. The historical succession of the main markers of the traditional culture is shown by way of examples of its various areas. In particular, it concerns the sections of the economic-industrial culture, trades and crafts, folk architecture, ethnic medicine, funeral ceremonial, etc. Thus, both of the ethnographic materials are vivid reflections of the Ukrainian ethnic and cultural heritage of the village of Oskil in the Izium region. Though they are recorded with an interval of almost a hundred years, one can state historical continuity of the preservation of folk memory as for the events of the last century, the markers of material and spiritual culture of Slobozhanshchyna representatives.